2015
DOI: 10.1007/978-1-4939-2778-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Dosimetry Modeling Using Computational Fluid Dynamics

Abstract: In this chapter, the current state of the art in modeling and prediction of aerosol deposition in respiratory systems using computational fluid dynamics (CFD) is presented and reviewed. First, the physical and chemical processes governing aerosol transport, evolution, and deposition are described followed by their coupling via fundamental conservation laws. The different ways to numerically model aerosol dynamics are then described and a brief overview of the different methods that can be used to obtain a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…, because of differences in the puffing parameters, the thermodynamic state of the flowing smoke/aerosol, and the geometry of the flow path in vitro and in vivo . Therefore, we have ongoing efforts in our group 90 , 91 that incorporate computational fluid dynamics models to further refine our knowledge and understanding of smoke/aerosol behavior in the human respiratory tract and in vitro systems – to eventually allow for more direct translatability between the culture systems and the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…, because of differences in the puffing parameters, the thermodynamic state of the flowing smoke/aerosol, and the geometry of the flow path in vitro and in vivo . Therefore, we have ongoing efforts in our group 90 , 91 that incorporate computational fluid dynamics models to further refine our knowledge and understanding of smoke/aerosol behavior in the human respiratory tract and in vitro systems – to eventually allow for more direct translatability between the culture systems and the in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…21,34 Particle coalescence (or coagulation), condensation/evaporation, and deposition (or filtration) are the key mechanisms that may profoundly change the nature of a liquid aerosol in experimental settings. [35][36][37] Coalescence is the process of clustering and merging of particles because of their collisions, leading to increases in size of newly created particles and to decreases in particle number density due to their merger. It can be linked to the relative motion of the colliding particles, mainly driven by diffusion (Brownian coalescence), but it can also be attributed to convection phenomena (e.g.…”
Section: Physical and Chemical Dynamics Of Aerosolsmentioning
confidence: 99%
“…For THS 2.2, it was concluded that glass beads were not necessary, as they only slightly improved the trapping efficiency of four carbonyls, while in the absence of glass beads, the trapping efficiency of acrolein and butyraldehyde was much better, and that of MEK and crotonaldehyde was slightly better. Further optimization of the trapping method was investigated by varying the number of sticks (4, 6, 8, or 10 3R4F cigarettes and 8, 10, 15, or 20 THS 2.2 sticks) and the volume of the trapping solution (20,25,30,36, or 40 mL PBS). The optimal PBS volume and number of test items, as determined by the levels of nicotine and eight carbonyls, were 36 mL PBS and 6 cigarettes for 3R4F, corresponding to approximately 1.8 puffs/ mL, and 40 mL PBS and 10 sticks for THS 2.2, corresponding to 3 puffs/mL.…”
Section: Aerosol Exposure Systems For In Vitro Studies: Submersed Celmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle size distribution gives information about the number and sizes of a flowing polydisperse aerosol. The amount of the delivered aerosol dose is directly linked to the particle size distribution because aerosol deposition is mainly controlled by the physical mechanisms that are dependent on the physical sizes of the particles (Nordlund and Kuczaj 2015).…”
Section: Aerosol Generation and Characterizationmentioning
confidence: 99%